Flood Early Warning System Prototype Based on Ultrasonic Sensor and Internet of Things - Muhammad Thoriq Arkaan Susila; Ilham Nadiyansyah Firdaus; Muhammad Farid Chuzairi; Dien Rahmawati (Universitas Syiah Kuala, 2023)
Floods that come all of a sudden cause many people to be unable to prepare themselves to deal with it, so material losses to health problems cannot be avoided. Therefore, a system is needed to provide early warning to the public before a flood occurs. As technology develops, water levels in an area can be monitored to anticipate flooding using the Internet of Things (IoT). IoT can help to monitor and warn of floods in real-time and continuously. In this research, the system will be placed in areas that often cause flooding. Monitoring results from sensor readings will be stored in the cloud database. The water level category is divided into 4 levels, namely “Safe”, “Standby”, “Careful”, and “Danger”. The system uses IoT and a database to send water level status to users as notifications on applications. The buzzer will sound as a warning sign when the water level enters the “Danger” status. The system test results show that the sensor has a very good level of accuracy with an error percentage of 0.242131%, and IoT connectivity can reach a distance of up to 20 meters.